Biological control of biofilms on membranes by metazoans. (1st January 2016) - Klein, Theresa; Zihlmann, David; Derlon, Nicolas; Isaacson, Carl; Szivak, Ilona; Weissbrodt, David G.; Pronk, Wouter
Abstract: Traditionally, chemical and physical methods have been used to control biofouling on membranes by inactivating and removing the biofouling layer. Alternatively, the permeability can be increased using biological methods while accepting the presence of the biofouling layer. We have investigated two different types of metazoans for this purpose, the oligochaete Aelosoma hemprichi and the nematode Plectus aquatilis . The addition of these grazing metazoans in biofilm-controlled membrane systems resulted in a flux increase of 50% in presence of the oligochaetes ( Aelosoma hemprichi ), and a flux increase of 119–164% in presence of the nematodes ( Plectus aquatilis ) in comparison to the control system operated without metazoans. The change in flux resulted from (1) a change in the biofilm structure, from a homogeneous, cake-like biofilm to a more heterogeneous, porous structure and (2) a significant reduction in the thickness of the basal layer. Pyrosequencing data showed that due to the addition of the predators, also the community composition of the biofilm in terms of protists and bacteria was strongly affected. The results have implications for a range of membrane processes, including ultrafiltration for potable water production, membrane bioreactors and reverse osmosis. Graphical abstract: Highlights: Metazoans in biofilm-controlled membrane systems lead to significant flux increase. The flux is increased by 119–164% in presence of nematodes ( Plectus aquatilis ). The flux is increased by 50% in presence of oligochaetes ( Aelosoma hemprichi ). The presence of the metazoans leads to a strong decrease of the basal layer. The community of protozoans and bacteria is affected by the metazoans.